Managing and Visualizing Your BIM Data Understand the Fundamentals of Computer Science for Data Visualization Using Autodesk Dynamo, Revit, and Microsoft Power BI. - Pellegrino, Ernesto (Packt Publishing, Limited, 2021)
Learn how to make optimum use of your BIM data using Dynamo to make better design decisions and create feature-rich dashboards using Power BI to track your model's data Key Features A go-to guide for AEC professionals to analyze and manage their data Explore popular use cases and best practices from experts around the world Create efficient dashboards using Dynamo and Power BI Book Description Business intelligence software has rapidly spread its roots in the AEC industry during the last few years. This has happened due to the presence of rich digital data in BIM models whose datasets can be gathered, organized, and visualized through software such as Autodesk Dynamo BIM and Power BI. Managing and Visualizing Your BIM Data helps you understand and implement computer science fundamentals to better absorb the process of creating Dynamo scripts and visualizing the collected data on powerful dashboards. This book provides a hands-on approach and associated methodologies that will have you productive and up and running in no time. After understanding the theoretical aspects of computer science and related topics, you will focus on Autodesk Dynamo to develop scripts to manage data. Later, the book demonstrates four case studies from AEC experts across the world. In this section, you'll learn how to get started with Autodesk Dynamo to gather data from a Revit model and create a simple C# plugin for Revit to stream data on Power BI directly. As you progress, you'll explore how to create dynamic Power BI dashboards using Revit floor plans and make a Power BI dashboard to track model issues. By the end of this book, you'll have learned how to develop a script to gather a model's data and visualize datasets in Power BI easily. What you will learn Understand why businesses across the world are moving toward data-driven models Build a data bridge between BIM models and web-based dashboards Get to grips with Autodesk Dynamo with the help of multiple step-by-step exercises Focus on data gathering workflows with Dynamo Connect Power BI to different datasets Get hands-on experience in data management, analysis, and visualization techniques with guidance from experts across the world Who this book is for This book is for BIM managers, BIM coordinators, design technology managers, and all AEC professionals who want to learn Autodesk Dynamo to analyze, manage, and visualize their BIM data as well as understand some associated computer science topics. You need to have a background in BIM and knowledge of what a BIM model is to make the most of this book.